Penyalahgunaan Data Pribadi Pada Pinjaman Online di Indonesia: Analisis Perlindungan dan Sanksi Hukum - Ardana , Sofia Tio; Kornelis, Yudi (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2024)
The increasing number of cases of illegal online loans raises concerns about consumers' vulnerability to the misuse of information containing personal data by perpetrators who have no responsibility when using it. This research was prompted by the increasing incidents of misuse of personal data, which pollutes users' privacy without explicit permission, as reported by victims of illegal online loans. The objective of this research is to analyze the significance of legal protection for personal data in online loan application services, as well as to evaluate the protection and sanctions mechanisms that apply in Indonesia. The research was conducted using normative juridical methods and sourced secondary data, which was studied qualitatively. The findings are as follows: (1) Criminal provisions for fintech operating illegally in Article 32 Juncto (jo), as well as Article 48 of the Law. The 2008 and 2016 regulations do not explicitly address the sanctions that should be imposed on illegal fintech. However, Article 26 of the ITE Law and POJK no. 77/POJK.01/2016 concerning Information Technology-Based Money Lending and Borrowing Services do regulate the legal protection of personal data. 77/POJK.01/2016 concerning Information Technology-Based Money Lending and Borrowing Services; (3) Legal sanctions related to cases of misuse of personal data in accordance with Article 47 paragraph (1) of Law no. 11 of 2008.